Study on structural robustness to resist progressive collapse of vertical irregularly base-isolated structures - Bao, Chao; Ma, Xiaotong; Lv, Dahai; Wu, Qiaozhi; Doh, Shu Ing; Chin, Siew Choo; Shu, Hongbo; Nor Hayati, Abdul Hamid (Elsevier Ltd, 2022)
It is necessary to establish qualitative analysis of structural robustness to ensure that the design meets the engineering requirements. The existing damage analysis methods such as Incremental Dynamic Analysis and Static Pushover Analysis which are used to determine the overall response of the structure without focusing on the local damage of the single structural component. From the macroscopic point of view, the local damage on each structural component can cause the progressive collapse of the overall structure and reduce the structural robustness. Particularly for the construction of special based isolation system and superstructure, the impact of accidental bearing failure on the overall structure of the impact of progressive collapse cannot be determined directly. This study starts with the damage risk and the importance of the single component, and the failure of the single component is related to the collapse of the whole structure. Based on the Alternative Load Path Method, the quantitative analysis method of structural anti-progressive collapse is proposed, and the vertical irregular base-isolated structures are compared and analyzed. The robustness of the isolated structure after the failure of the isolated bearing is discussed. The result shows that, qualitative analysis of structural robustness proposed in this study can be used to provide reference for the selection of building scheme and analysis of structural robustness. The robustness of the structure does not only depend on the property of structure itself but also the external load applying on the structure. It is suggested that reasonable protection measures should be set for the isolation bearing with greater vulnerability coefficient which may suffer from extreme accidents and the potential risk of isolation bearing with greater component importance coefficient is eliminated or reduced.